AWARENESS OF THE ANTI-PHOTO AND VIDEO VOYEURISM ACT OF 2009 (RA 9995) IN SELECTED UNIVERSITIES IN PALAWAN - Bungay, Hannah Mae; SALVIEJO, KYLA MAE (Studies in Technology and Education, 2024)
The early exposure of individuals to the use of technology may lead to the dangers of internet pornography sites and materials. Since scrolling social media platforms has become a pastime of every learner in this generation, it is essential to guide them to have responsible online conduct and avoid voyeuristic behaviors. Thus, this study aimed to determine the level of awareness of the learners in the existence of laws that can protect or prohibit them from such violence, specifically the Anti-Photo and Video Voyeurism Act of 2009 (RA 9995). This study adopted a descriptive research design and employed a random sampling technique to select 100 respondents from three universities in Palawan. The survey instruments utilized in this investigation were disseminated via survey forms using Google Forms. The descriptive analysis was used to identify respondents' awareness levels in RA 9995. Findings revealed that respondents' level of awareness about the law was "not aware," which means that most of them are unaware of the existence of RA 9995. The study's findings would reference the faculty and staff of the College Universities in Puerto Princesa, Palawan, if possible, in their extension program.